The engineered subject as an ethical achievement throughout the capabilities while positive freedoms according to Amartya Sen - Maceri, Sandra Beatriz (2020)
This paper reconstructs the senean bond among equality of opportunities, development and expansion of capabilities as well as their foundation. Sen states that equality of opportunities promotes development and this only occurs if capabilities or real freedoms are expanded. Development is an expanding process of the real freedoms towards people. This freedom is individual but it must include the freedom of all other people. Moreover, it is an individual freedom with social commitment. Following this idea, Sen raises the discussion on equal opportunities to an ethical field. The ethical management of the agent, which achievement is the engineered subject, is possible and necessary throughout the key conceptions of Amartya Sen linked as it is uttered in this analysis.